2016
DOI: 10.1021/acs.macromol.6b00595
|View full text |Cite
|
Sign up to set email alerts
|

Dominant β-Form of Poly(l-lactic acid) Obtained Directly from Melt under Shear and Pressure Fields

Abstract: Shear and pressure fields unavoidably coexist in practical polymer processing operations, but their combined influence on the crystalline structure of poly(L-lactic acid) (PLLA) has never been studied due to the limit of experiment device. In the current work, we utilized a homemade pressuring and shearing device to study the crystalline morphology and structure of PLLA under the coexistence of shear and pressure. Interestingly, we obtained almost exclusive β-form directly from PLLA melt crystallization at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 54 publications
1
89
0
Order By: Relevance
“…The experiments were performed by using PSD (a detailed description of the PSD was released in our previous articles) . PSD can simultaneously impose flow and pressure on the polymer melt, where the shear rate increases linearly with radius ( r ) (see the Figure a [trueγ˙()r=italicωr/d, where ω stands for the angular speed, and d is the gap, 0.5 mm].…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…The experiments were performed by using PSD (a detailed description of the PSD was released in our previous articles) . PSD can simultaneously impose flow and pressure on the polymer melt, where the shear rate increases linearly with radius ( r ) (see the Figure a [trueγ˙()r=italicωr/d, where ω stands for the angular speed, and d is the gap, 0.5 mm].…”
Section: Methodsmentioning
confidence: 78%
“…Meanwhile, pressure has been revealed to slow down the crystallization kinetics, generate new crystal forms, and trigger the formation of extended chain crystals . Even though flow‐ and pressure‐induced crystallization have been well elucidated, the available theories of structure evolution under the coexistence of flow and pressure are rarely established ascribed to diverse challenges as documented in the previous articles …”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, the experimental results obtained in the conditions without considering influences of pressure cannot reflect the real situation, so cannot effectively guide practical processing. Moreover, our previous studies demonstrated that for iPP and PLLA there were notably different crystallization behavior when simultaneously applying flow and pressure . Ru et al .…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, our previous studies demonstrated that for iPP and PLLA there were notably different crystallization behavior when simultaneously applying flow and pressure . Ru et al . obtained β‐form directly from PLLA melt at a shear rate of 13.6 s −1 and under a pressure of 100 MPa for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…However, the combined effects of pressure, flow, and CNTs on γ‐phase formation of iPP still have not been well understood, which arouses our great interest in exploring the crystallization behaviors of iPP. Therefore, we used a homemade pressurizing and shearing device (PSD), which was introduced in detail in our group's previous work . With such a unique device, we were able to carry out a series of study of γ‐form formation for iPP/CNTs composite under coexistence of varies shear flow and pressures.…”
Section: Introductionmentioning
confidence: 99%